A Rare Case of Calcified Simple Mesenteric Cyst in a 70-Year-Old Woman - Alazar Berhe Aregawi; Alemwosen Teklehaimanot Alem (Case Reports in Surgery)
Mesenteric cysts are one of the rare causes of intra-abdominal masses. They account for 1 in 100,000 cases in adults and 1 in 20,000 cases in children. Mesenteric cysts are commonly found in the small intestine, up to 60% of cases, and occasionally in the colon. The clinical presentation of patients with mesenteric cysts is so variable and nonspecific. It ranges from being asymptomatic to features of acute abdomen very rarely. Surgery is the treatment of choice. Complete excision with negative margins plays a curative role in avoiding the risk of recurrence as well. Here, we present the case of a 70-year-old woman who came to Hawassa University Comprehensive Specialized Hospital with abdominal swelling for a 5-month duration. She had an abdominal ultrasound, which suggested a calcified mesenteric cyst with internal hemorrhage. The patient was taken to the OR with the impression of an intra-abdominal mass for exploratory laparotomy. The mass was completely excised and was subjected to pathology, which turned out to be a calcified simple mesenteric cyst, and the purpose of this case report is to alert physicians that although the preoperative diagnosis of mesenteric cysts is difficult, it should be considered in the differential diagnosis of a patient presenting with an intra-abdominal mass.